COLITECVS – NEW TOOL FOR AUTOMATED REDUCTION OF PHOTOMETRIC OBSERVATIONS - Savanevych, V. E.; Briukhovetskyi, O. B.; Khlamov, S. V.; Pohorelov, A. V.; Vlasenko, V. P.; Dubovsky, P. A.; Kudzej, I.; Parimucha, Š. (Одеські астрономічні публікації, 2017)
The capabilities of telescopes allow us to make the plotting of light curves a routine task. This one shifts the main attention of astronomer from the plotting to research. To achieve this goal, we developed a new tool for automated reduction of photometric observations, which includes the computational method for the brightness assessment of the investigated and comparison stars; brightness equalization of astronomical images using inverse median filter; light curve plotting and its processing using different tools.